Exploring Cloud-Based e-Learning Adoption in Developing Nations: A Comprehensive Review - Khalilullah Khalid; Rajashree Jain (Journal of Applied Engineering and Technological Science (JAETS), 2026)
Digital transformation in the form of Cloud-based e-learning (CBEL) in higher education has enabled anytime, anywhere learning environments. The literature on the adoption models for CBEL from developing nation’s perspectives is scarce. A current study presents a systematic literature review of CBEL adoption in developing nations. The PRISMA framework was used for the study. It articulates 27 different articles published during 2019-2025. The articles were chosen from Scopus and WoS databases. The review presents user intention to adopt to CBEL as high, but actual adoption depends on a number of contextual factors such as infrastructure, connectivity, training, support, security and policy. The review further reveals a strong reliance on user-level models such as TAM and UTAUT, with limited integration of organizational perspectives and reliance on perceptual measures over actual outcomes. Consequently, this study proposes an integrated framework combining technological readiness, organizational support, user acceptance, and adoption outcomes. Theoretically, CBEL adoption in developing countries cannot be explained only through user acceptance factors but also by organizational and infrastructural conditions. From a practical perspective, HEIs administrators and policymakers should view CBEL as a sociotechnical system, not only a digital tool. Future research should focus on longitudinal empirical validation of the proposed framework.